The effect of soil stiffness variations on Tunnel Lining Internal Forces under seismic loading and Case comparison with existing analytical methods - Zamani, Reza; Motahari, M.R. (Ciência e Natura, 2015)
Closed-form solutions are of great interest for quick and accurate evaluation of stresses and displacements around underground excavations. Dynamic effects on underground structures have often been neglected based on the assumption that their response to earthquake loading is relatively safe as compared to that of surface structures. Nevertheless, several examples of recorded damage to underground structures for which seismic forces were not considered in the original design. Therefore, during the seismic excitement, tunnels are basically subjected to three kinds of deformation : axial compression and extension, longitudinal bending and ovaling or racking. In the present investigation a series of numerical analyses under the influence of soil hardness parameters based on no-slip between soil and tunnel lining were performed, using finite element code PLAXIS, and outputs were compared with result of analytical solutions.